2016
DOI: 10.1039/c6py00725b
|View full text |Cite
|
Sign up to set email alerts
|

All-thiophene-based conjugated porous organic polymers

Abstract: Novel all-thiophene-based conjugated porous organic polymers (ThPOP-1 and ThPOP-2) were synthesized through ferric chloride-catalyzed oxidative coupling polymerization at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 56 publications
(65 reference statements)
1
31
0
Order By: Relevance
“…The polymers were also characterized at the molecular level by solid state 13 C crosspolarization magic‐angle spinning (CP/MAS) NMR spectroscopy (Figure S2, Supporting Information). The peaks in the chemical shift ranging from 115 to 155 ppm correspond to the carbon atoms in thiophene rings, which agree with the reported thiophene‐containing polymers very well . Both polymers displayed high thermal stability up to about 400 °C in nitrogen atmosphere (Figure S3, Supporting Information).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The polymers were also characterized at the molecular level by solid state 13 C crosspolarization magic‐angle spinning (CP/MAS) NMR spectroscopy (Figure S2, Supporting Information). The peaks in the chemical shift ranging from 115 to 155 ppm correspond to the carbon atoms in thiophene rings, which agree with the reported thiophene‐containing polymers very well . Both polymers displayed high thermal stability up to about 400 °C in nitrogen atmosphere (Figure S3, Supporting Information).…”
Section: Resultssupporting
confidence: 86%
“…PT has a linear polymer structure, while P33DT is a crosslinked polymer network because of the difference of the monomers employed. Fourier transform infrared spectrometer (FT‐IR) spectra of the polymers confirmed the polymer structures as evidenced by the vibration of CH bonds in the aromatic structure at 2814–2976 cm −1 (Figure S1, Supporting Information), the unsaturated CC stretching vibration at around 1632 cm −1 , aromatic stretching bands at 1483 and 1385 cm −1 , and the stretching vibration band of CSC at around 1090 cm −1 . The polymers were also characterized at the molecular level by solid state 13 C crosspolarization magic‐angle spinning (CP/MAS) NMR spectroscopy (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 82%
“…The signal at 141 ppm corresponds to the carbon of ethylene. The peak at 136 ppm and the broad peak at 128, 124 ppm can be ascribed to carbons on thiophene ring . SEM and TEM images revealed that the polymer PTTE has a solid spheres morphology (Figure c,d).…”
Section: Resultsmentioning
confidence: 96%
“…Despite the versatile applications of CPPs in CO2 capture, energy storage, and catalysis, these polymers have been most commonly synthesized under thermally and chemically harsh reaction conditions which are often energy intensive and require corrosive reagents. For instance, the majority of thiophenebased CPPs reported in the literature have been synthesized by conventional C-C coupling reactions such as ferric chloride catalyzed oxidative coupling, 30,[127][128][129][130][131] and Sonogashira-Hagihara polymerization. [132][133][134] Despite its moderate reaction conditions, the oxidative coupling has been reported to yield chlorinated polymers 128 with residual iron salts.…”
Section: Limitations Of Conventional Synthesis and Scope Of Direct Armentioning
confidence: 99%
“…For instance, the majority of thiophenebased CPPs reported in the literature have been synthesized by conventional C-C coupling reactions such as ferric chloride catalyzed oxidative coupling, 30,[127][128][129][130][131] and Sonogashira-Hagihara polymerization. [132][133][134] Despite its moderate reaction conditions, the oxidative coupling has been reported to yield chlorinated polymers 128 with residual iron salts. 135 whereas Sonogashira polymerization requires pre-functionalization of C-H bonds with toxic and flammable reagents like organosilanes and is limited to monomers containing terminal ethynyl groups.…”
Section: Limitations Of Conventional Synthesis and Scope Of Direct Armentioning
confidence: 99%